693 Sleep Health in the Young Adult Clinic: A retrospective observational cohort study. (3rd May 2021) - Eissa, Mohamed; Bansal, Shikha; Bosma, Rachael; Sheffe, Sarah; Law, Yen Shuang; Mcloone, Mary; Di Renna, Tania; Singh, Mandeep
Abstract: Introduction: The Toronto Academic Pain Medicine Institute (TAPMI) Young Adult Clinic (YAC) was developed to offer transition services for clients aged 17–25 with persistent pain. It was noticed that YAC patients had significant problems with their sleep and the program was expanded in January 2019 by including a sleep medicine specialist for systematic evaluation of sleep health. Long-term sleep disruption has been associated with increase sensitivity to pain, prolonged pain duration, and predicts chronic pain. The degree of pain relief can directly impact the quality and disruption of sleep. Methods: After approval from institutional review board, we reviewed YAC medical charts from March 2018 to April 2019 and extracted information pertaining to demographics, chronic pain and sleep. We present here the preliminary data of our multidisciplinary clinic Results: 55 medical charts were reviewed which included 40 females, 13 males, 2 nonbinary individuals, with a mean age of 20.3±2.4 years. 53% of the patients had chronic widespread pain. Symptoms of or disorder of sleep were reported in 72.7% of the patients. The various nighttime disorders of sleep were trouble falling asleep, insomnia, problems with sleep initiation, difficulty in maintaining sleep, poor sleep continuity, frequent night awakenings due to pain, restless leg syndrome (RLS), obstructive sleep apnea, parasomnic behavior, circadian rhythm disorder such as delayed sleep phase disorder. As assessed by Epworth Sleepiness scale, 7% of the patients had mild, 7% had moderate and 2% had severe daytime sleepiness. 42% of the youths demonstrated a low self-efficacy score as per Pain Self Efficacy Questionnaire (PSEQ). Patient Health Questionnaire (PHQ-9) was used to measure the severity of depression which showed that 5.5%, 27%, 18%, 14.5%, 22% of the YAC patients suffered from minimal, mild, moderate, moderately-severe and severe depression respectively. The information collected on Pain Catastrophizing scale (PCS) suggested that 24%, 29% and 31% were at low, moderate, and high risk respectively in having catastrophizing thoughts and feelings related to pain. There was no statistical difference in the means PSEQ, PHQ-9 and PCS scores of young adults. Conclusion: Sleep disturbances may be an important modifiable risk factor for alleviating distress in young adults with chronic pain. Support (if any):